Playing games to save water: Collective action games for groundwater management in India - Meinzen-Dick, Ruth S.; Janssen, Marco A.; Kandikuppa, Sandeep; Chaturvedi, Rahul; Rao, R. Kaushalendra; Theis, Sophie (Arizona State University, 2017)
Groundwater is one of the most challenging common pool resources to govern, resulting in resource depletion in many areas. We present an innovative use of collective action games to not only measure propensity for collective action, but to improve local understanding of groundwater interrelationships and stimulate collective governance of groundwater, based on a pilot study with NGOs in Andhra Pradesh, India. The games simulate crop choice and consequences for the aquifer. These were followed by a community debriefing, which provided an entry point for discussing the interconnectedness of groundwater use, to affect mental models about groundwater. A slightly modified game was played in the same communities, one year later. Communication within the game increased the likelihood of groups reaching sustainable extraction levels in the second year, but not the first. Individual payments to participants based on how they played in the game had no effect on crop choice. Either repeated experience with the games or the revised structure of the game evoked more cooperation in the second year, outweighing other factors such as education, gender, and trust index scores. After the games were played, a significantly higher proportion of communities have adopted water registers and rules to govern groundwater, compared to other communities in the same NGO water commons program. Because groundwater levels are affected by many factors, games alone will not end groundwater depletion, but can contribute to understanding of the role of crop choice and collective action, to motivate behavior change toward more sustainable groundwater extraction.